MENGGAGAS PERENCANAAN KURIKULUM MENUJU SEKOLAH UNGGUL - Saufi, Akhmad; Hambali, Hambali (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2019)
Excellent school is identical with quality school. Many people assume that to become a Excellent school must have large financial capital because the availability of facilities and capable resources require big costs. This statement is not entirely true, because besides facilities and human resources involved in educational activities, the most important part of education is the curriculum. This paper aims to find out how curriculum planning ideas can be applied in excellent school. The curriculum as a medium for achieving educational goals also serves as the main guideline for implementing learning activities. Therefore, the design of the curriculum in education must be positioned as a platform for schools to develop education. The results of the author's analysis describe that the curriculum planning framework in excellent schools is developed from local-regional to national level. Curriculum planning process must pay attention to the holistic approach and eliminate hierarchies in decision making. The socio-cultural approach is also essential by involving competent human resources including teachers as curriculum implementers.